Research on the formation of low-environmental-burden area and organization by the activity of environmental management - SASATANI, YASUYUKI; HIRAI, TAKAHARU; KOMORI, MASAYA (ENVIRONMENTAL SYSTEMS RESEARCH, 2000)
We analyzed and compared environmental stance of a private enterprise and a basic self governing body which positively carry out environmental policies. We tried the valuation andtype of their environmental-activity again, and found the process of their actions for environmental problem. First step is to take the lead in improving a direct influence for environment. Second step is for a concern to take part in the performance to improve a indirect influence for environment. Third step is to improve the environmental burden in partnership with the various subjects. With keeping above-stated contents in their mind, it is important to form low-environmental-burden area.